The complete mitochondrial genome of the Bechstein's bat, Myotis bechsteinii (Chiroptera, Vespertilionidae). Issue 1 (1st January 2017) - Jebb, David; Foley, Nicole M.; Kerth, Gerald; Teeling, Emma C.
Abstract: In this study, we present the complete mitochondrial genome of the Bechstein's bat, Myotis bechsteinii . The mitogenome is 17, 151 bp in length and is AT-rich with base composition A (27.8%), C (22%), G (16.1%), and T (34.1%). The mitogenome shows conserved gene content and order similar with other mammalian mitogenomes, being composed of 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and one control region. The majority of genes are encoded on the H-Strand except for ND6 and 8 tRNAs as found in other bat species. The field identification of Myotis bechsteinii was confirmed by phylogenetic analyses using datasets comprising whole mitogenomes and COXI . This mitogenome is a resource for future studies of Myotis bats and other mammals.